May Grace Abound: Making God's Grace Cognitively Salient May Increase Reparative Action. Issue 3 (September 2020) - Bassett, Rodney L.; Scott, Sarah; Blodgett, Renee; Barnhart, Mika; Batterson, Noelle; Hall, Ashley; Pursel, McKennzie; Emerson, Melissa
A study was done with Christian college students to determine the relationship between grace salience, remorse, and reparative action in the context of a past transgression. Grace salience involves the process of making God's grace cognitively prominent. In the context of dual-process modeling, grace salience involves making the construct of God's grace cognitively explicit and the focus of attention for an individual. Participants recalled a past experience where they harmed someone. Before the grace salience or control intervention, there were no differences in desire for reparative action and guilt or shame self-statements. However, after the intervention, compared to the control, the grace salience intervention produced a greater desire for reparative action and greater tendency to agree with guilt self-statements. When feelings of remorse were assessed after the experimental manipulations, higher levels of sorrow and brokenness predicted greater desire for reparative action, higher levels of shame and brokenness predicted higher agreement with shame self-statements, and higher levels of guilt and brokenness predicted greater agreement with guilt self-statements.